2008
DOI: 10.1007/s10641-008-9432-9
|View full text |Cite
|
Sign up to set email alerts
|

Migration of green sturgeon, Acipenser medirostris, in the Sacramento River

Abstract: Adult green sturgeon, Acipenser medirostris, were collected in San

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 10 publications
2
68
0
Order By: Relevance
“…Furthermore, it is unlikely that any sturgeon died as a result of the operation. In a later study of the species' movements region-wide, 96 green sturgeon were tagged using similar tagging procedures with no known mortality (Heublein et al 2009). A description of the entire tagging study, including analysis of observed green sturgeon distribution and movements with respect to environmental parameters such as depth, temperature, salinity, and dissolved oxygen, Table 1 Results of comparison of measured San Francisco Bay tidal flows to those predicted by current model.…”
Section: Fish Orientation To Currentmentioning
confidence: 99%
“…Furthermore, it is unlikely that any sturgeon died as a result of the operation. In a later study of the species' movements region-wide, 96 green sturgeon were tagged using similar tagging procedures with no known mortality (Heublein et al 2009). A description of the entire tagging study, including analysis of observed green sturgeon distribution and movements with respect to environmental parameters such as depth, temperature, salinity, and dissolved oxygen, Table 1 Results of comparison of measured San Francisco Bay tidal flows to those predicted by current model.…”
Section: Fish Orientation To Currentmentioning
confidence: 99%
“…Ultrasonic tags have been used to track the movements of salmon (Welch et al 2008) and sturgeon (Kelly et al 2007; Heublein et al 2009) in rivers and coastal-estuarine environments, to track the short-scale movements of several sharks (Holland et al 1992; Klimley 1993; Klimley et al 2002; Klimley and Nelson 1984) and rays (Klimley et al 2005), and to study site fidelity of sharks at seamounts (Klimley and Nelson 1984) and tuna at fish aggregating devices (FADs) (Klimley and Holloway 1999). In 2006, a regional network of scientists in the ETP deployed arrays of hydrophones at sites around Cocos, Galapagos, and Malpelo Islands (see www.migramar.org) and began an ambitious study to understand local and regional movement patterns of several shark species, including scalloped hammerhead sharks.…”
Section: Introductionmentioning
confidence: 99%
“…We also must determine how residency time in a particular habitat affects element deposition [182]. Sturgeon are capable of fairly rapid movements between habitat types [79], [186], [187] and it is uncertain if these movements would be represented accurately in otolith or pectoral fin ray elemental “fingerprints.” Also, it will be important to characterize the rate at which elemental profiles within particular locations vary, as rapid rates of naturally or anthropogenically induced environmental change may reduce our ability to accurately reconstruct the movement of individuals over longer timeframes using otoliths and fin rays [188]. These uncertainties should be addressed prior to a broad application of microchemical techniques toward addressing questions regarding sturgeon movement and habitat preferences.…”
Section: Research Techniquesmentioning
confidence: 99%
“…Green Sturgeon were also shown to have diverse patterns of migration within and among populations. Within the Sacramento River, acoustic tags revealed that a seasonal water diversion dam was a serious impediment to the spawning migration of Green Sturgeon [37]. Habitat data associated with tag detections was used to gain further insight into freshwater [38] and fine− [39] and coarse-scale [40] marine habitat preferences and seasonal patterns of distribution.…”
Section: Introductionmentioning
confidence: 99%